Mind your language. - Croser, Joe (Architects' Journal, 2004)
Looks into the Industry Foundation Classes or IFC descriptions, a language for exchange of CAD data developed by the International Alliance for Interoperability. Discussion of the inter-disciplinary data sharing; Strategies made by the government of Singapore to modernize the way the architectural community makes buildings; Expectation of John Mitchell of Graphisoft that IFC will be widely used by architects.